(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The work discusses the question of the systematic status of the original Bombus genus and the different viewpoints regarding its successive distribution into genera and subgenera. Then follows an illustration of the male genitalia of 10 species of the genus, since this morphological feature is of great discriminatory importance. The principal chromatic characteristics of the species under consideration are provided: 5 species belong to the section Odontobombus, that is distinguendus Morawitz, inexpectatus Tkalcu, muscorum (Fabr.), subterraneus (L.), sylvarum (L.); 5 species belong to the section Anodontobombus, that is jonellus (Kirby), lucorum (L.), monticolus Smith, patagiatus Nylander, wulfeini Radoszkowski.